Clinical usefulness of anti-cell membrane DNA autoantibodies in serology negative systemic lupus erythematosus - Awang Kechik, Faten Nurul Amira; Abdullah, Maha; Arip, Masita; Hassan, Masriana; Mahayidin, Hasni (Malaysian Society of Pathologists, 2021)
Introduction: Systemic lupus erythematosus (SLE) diagnosis is dependent on the detection of serum autoantibodies. To date, there is no autoantibody highly sensitive and specific enough to be considered as a gold standard. This study aimed to determine the diagnostic usefulness of anti-cmDNA antibodies which found to be associated with SLE. Materials and methods: Serum samples from 83 SLE, 86 other connective tissue diseases (OCTD) and 61 healthy subjects were randomly selected for the study. The OCTD cases included 56 rheumatoid arthritis, 12 scleroderma, 10 Sjogren's syndrome and 8 mixed connected tissue diseases. All samples were assayed for anti-cmDNA by indirect immunofluorescence assay (IFA) using Raji cells as substrate. SLE samples were also tested for antidsDNA and anti-Sm antibodies using enzyme-immunoassays. Results: Anti-cmDNA positivity was highest in SLE (55.4%) compared to OCTD (9.3%) and healthy subjects (0%). It was 100% specific at differentiating SLE from healthy subjects and 90.7% specific at differentiating SLE from OCTD. There were no significant differences in the sensitivity (55.4%) of anti-cmDNA at differentiating SLE from OCTD and healthy groups. Anti-cmDNA was present in 52.9% of SLE samples negative for standard SLE-specific autoantibodies. It was detected in 7 (36.8%) of anti-dsDNA, 25 (52.1%) of anti-Sm and 5 (31.3%) of both anti-Sm and anti-dsDNA negative samples. Anti-cmDNA positive SLE was significantly associated with arthritis (p=0.019). Conclusion: The high specificity of anticmDNA detection by IFA makes it an excellent diagnostic test for SLE. Anti-cmDNA is also useful for identifying SLE with negative anti-dsDNA or/and anti-Sm antibodies.